Sistem Informasi Manajemen Persediaan Berbasis Web di CV. Makmur Sejahtera Palopo - Aqilah, aqilah al afif fadhil; Bustamin, syamsumar; Sultan sahrir, Sukmawati (LPPM Universitas Dinamika Bangsa, 2023)
This study discusses the application of information technology-based stock management information systems at CV. Makmur Sejahtera is a trading company that focuses on air compressor trading. Currently, the company still uses a manual stock management system, which causes several problems, including delays, inaccurate stock data, and errors in recording. The waterfall method is used as a systematic approach in software development. The steps taken include needs analysis, planning, modeling, construction, and handing over the system to the user. Based on the needs analysis, the interface design is created using the Unified Modeling Language (UML), including Use Case Diagrams and Class Diagrams. The proposed information system has various features, including the management of users with different access rights, tracking stock data in real time, monitoring incoming and outgoing goods, and generating invoices. It is hoped that with the implementation of this system, CV. Makmur Sejahtera can improve efficiency and accuracy in its stock management so that it can compete better in the global market.